Perancangan Meja Multifungsi untuk Mahasiswa Desain Interior di Apartemen Tipe Studio - Cyndy Anggun Lumakso; Andereas Pandu Setiawan; yohan santoso (Intra, 2016)
The studio apartments attract many university students, other than as a place that's large enough to house a person, the strategic location makes it convenient for an alternative home. Interior designer is one profession that is much in demand today. Many young people seek to become interior designers as their final level education. Within a limited space of area and variety of activities, interior design students often have difficulty completing their tasks. Therefore, it is necessary to have a multi-functional desk to facilitate all the necessity of an interior design student.